Curriculum Of Love As The Foundation Of Character Education A Qur’anic Perspectiv - Muhamad Akip; Zuhri; Sujarwo; Windi Handika; Wisnu Adi Witjoro (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study aimed to analyze the strategies of Islamic Religious Education (IRE) teachers in enhancing students’ religious literacy. The focus of the research was on the planning, implementation, supporting and inhibiting factors, and the implications of teacher strategies for students’ religious literacy. This research used a qualitative descriptive approach with data collected through observation, interviews, and documentation. Data were analyzed through the stages of reduction, display, and conclusion drawing. The findings indicated that in the planning stage, teachers designed learning activities by integrating religious literacy into both classroom instruction and extracurricular programs. In the implementation stage, teachers applied various strategies such as project-based learning, the habituation of religious practices, and the use of digital media to strengthen students’ engagement. Supporting factors included school facilities, parental involvement, and students’ motivation, while inhibiting factors consisted of limited instructional time, variations in students’ literacy levels, and technological challenges faced by teachers. The study concluded that the strategies of IRE teachers significantly improved students’ abilities in reading, understanding, and applying Islamic teachings in daily life. Moreover, these strategies fostered a culture of religious literacy and strengthened students’ religious character. The results of this study implied that such strategies could serve as a model for other schools and suggested future research to explore the long-term impacts of religious literacy programs.